Tax audit and tax productivity in Lagos state, Nigeria - Clement Olatunji Olaoye; Stephen Ayodeji Ogunleye; Festus Taiwo Solanke (Emerald Publishing Limited, 2018)
The purpose of this paper is to examine the impact of the tax audit on tax productivity in Lagos state, Nigeria. Specifically, the study analyzed trends of tax audit and tax productivity, and the impact of Desk audit, Field audit and Back-duty audit on tax productivity in Lagos state.The study made use of both primary and secondary data. Primary data used in the study were collected with the use of questionnaires administered to 350 randomly selected staffs of Lagos state Internal Revenue Services, while secondary data used in the study were sourced from Federal Inland Revenue Service and Lagos Internal Revenue Service audit division in Lagos state over the period spanning from 2000 to 2015. Data collated in the study were analyzed descriptively using inferential methods such as unit root test, and estimation techniques such as Fully Modified Least Square (FMOLS) co-integration regression and Logit regression analysis.The study revealed that Field tax audit, desk tax audit and Back duty tax audit exert a significant positive impact on tax productivity with reported estimate of 0.530454 (p=0.0044<0.05) for FIDAUD, 0.774450 (p=0.0085< 0.05) for DEKAUD, 1.244317 (p=0.0001<0.05) for BAKAUD.Relevant tax authority (RTA), tax auditors and FIRS staff members should have full knowledge of modern audit tools like Computer Aided Audit Tools (CAATs) to enhance performance and maximum tax revenue generation.The study concluded that tax audit enhances the level of productivity of tax administration in Lagos state and that any form of tax audit has the tendency of influencing revenue accruing to the government from taxation positively. Hence, tax audit should be carried out on a routine basis to ensure that actual revenue collected is what the RTA remits to the government. Tax audit department should be given autonomy to carry out their responsibilities effectively.Tax audit should be carried out on a routine basis to ensure that actual revenue collected is what the RTA remits to the government. Tax audit department should be given autonomy to carry out their responsibilities effectively.This tax audit and tax productivity in Lagos state, Nigeria, fulfills an identified need to study how brand-supportive behavior can be enabled.